The role of loan agreements in the legal system of a constituent entity of the Russian Federation - Timatkov V. D., Lenkovskaia R. R. (Innovative approaches to management in economic, technical and legal systems, 2024)
This article is devoted to the study of the role of loan agreements in the legal system of a constituent entity of the Russian Federation. The purpose of the study is to consider the problem of the relationship between loan agreements and other legal institutions, such as civil law, banking law, consumer law and others. Particular attention is paid to the peculiarities of the conclusion, execution and termination of loan agreements at the level of a constituent entity of the Russian Federation. The features of regulation of credit relations at the regional level are analyzed, based on regulations and legislation of a specific subject of the Russian Federation. The authors analyze practical problems that arise when concluding loan agreements and resolving disputes between the parties. The influence of federal legislation on the regulation of credit relations in a specific constituent entity of the Russian Federation is also considered. Results. As a result of the above study, the author
Keywords: кредит; credit; правовая система; кредитные отношения; кредитный договор; роль кредитных договоров; legal system; loan agreement; credit relations; the role of loan agreements